PENGARUH KOMUNIKASI SOSIAL KODIM 0705/MAGELANG TERHADAP PENINGKATAN NASIONALISME GENERASI MUDA : Studi di SMA N 2 Kota Magelang - Supriyono, Tjatur; Burhanudin, Sambas; Natakertapati, Jihad (PPM Sdirjianbang Akademi Militer, 2024)
The younger generation is the main driving force behind Indonesia's independence as it is today, certainly accompanied by a strong sense of nationalism since the movement in 1908 up to the present. However, along with the advancement of time and the unstoppable wave of globalization, the nationalism of the younger generation is actually declining. The Military District Command 0705/Magelang Has become one of the means to rekindle the spirit of nationalism among the youth, which has begun to wane, through territorial development activities. One of them is social communication implemented through school extracurricular activities. This research aims to determine the extent of the decline in nationalism among today's youth, particularly at 2nd High School Magelang, and to assess the impact of social communication from the Military District Command 0705/Magelang soldiers in efforts to enhance the sense of nationalism among today's youth. This study employs a quantitative method and uses simple random sampling, meaning the researcher intentionally selects respondents randomly without considering specific strata. The data collection method was carried out by distributing questionnaires. The research results indicate that there are several students at 2nd High School Magelang who still have a low sense of nationalism. One effort to enhance the students' sense of nationalism is through social communication methods by Military District Command 0705/Magelang. One of the social communication activities conducted by Military District Command 0705/Magelang is through regular extracurricular training held both at 2nd High School Magelang and at Military District Command 0705/Magelang. Then, in terms of calculations, social communication and the enhancement of nationalism are directly proportional, so it can be said that the social communication carried out by the soldiers of Military District Command 0705/Magelang has an influence on increasing the sense of nationalism among the students of 2nd High School Magelang.